The Influence of Macroeconomic Factors on The Indonesia Stock Price Index at Consumer Goods Sectors - Syakira, Anindya Alya; Kassim, Aza Azlina Md; binti Mohd Tarmizi, Raudhah (Journal of Applied Management Research, 2025)
The capital market has a tremendous role in supporting the economic cycle since it can match individuals who have more money and those who need it. The capital market can be used as an investing-absorbing instrument and as tool to strengthen the financial position. In actuality, the capital market has taken a place as a financial nerve on the contemporary global economy. The purpose of this study is to determine the macroeconomic factors on The Indonesia Stock Price Index at sub-sector cosmetic and household industry. Specifically, this study aims to investigate the effect of inflation, BI rate, exchange rate, gold prices, and economic growth on The Indonesia Stock Price Index sub-sector cosmetic and household industry for the period of 2019-2021. As for methodology, secondary data was collected from the official website of The Indonesia Stock Exchange, Bank Indonesia official website, and the financial services authority which processed through the SPSS application. By using a multiple regression analysis tool, the data was processed. The findings revealed that inflation, BI rate, and gold prices have a significant impact while exchange rate and economic growth do not have a significant impact on The Indonesia Stock Price Index sub-sector cosmetic and household industry. This study also includes a discussion, limitations, recommendations, and conclusions.